New analytical procedure for seismic analysis of reinforced retaining wall with cohesive-frictional backfill. Issue 6 (December 2010) - Ghanbari, A.; Ahmadabadi, M.
Abstract : ABSTRACT: A simple analytical method is proposed for analysis of reinforced retaining walls with cohesive-frictional backfill under pseudo-dynamic loadings. The suggested formulation for n layers (slices), including 5 n equations and 5 n unknowns for analysis of each retaining wall, is presented based on limit equilibrium principles and the horizontal slices method. The angle of the critical failure wedge, the tensile force in the reinforcements and distribution of active earth pressure along the height of wall can all be determined in each moment of loading using this method. The results of the analysis indicate that seismic active earth pressure has a nonlinear distribution in cohesive-frictional soils. Also, the results reveal that the period of seismic load is of considerable influence on the tensile force in the reinforcements. Moreover, comparison of results reported by other researchers with those of the suggested method shows a small difference between them in most cases. Finally, it has been concluded that the proposed analytical procedure reliably calculates the resultant seismic earth pressure and its distribution, the tensile forces in the reinforcements, and the angle of failure wedge for unreinforced and reinforced walls in cohesive-frictional soil.